Republic of Kosovo : Technical Assistance Report- Public Investment Management Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
Republic of Kosovo:Technical Assistance Report- Public Investment Management Assessment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet